The Effect of Round Robin Strategy Towards Students Reading Comprehension at Class X Darul Fatah Islamic Boarding School - Padila, Muhammad; Marleni, Lusi; Ayu, Citra (Journal of English Language and Education, 2026)
This study aims to investigate the effect of the Round Robin strategy on students’ reading comprehension at Class X of Darul Fatah Islamic Boarding School. Reading comprehension is a fundamental skill in English learning, as it enables students to understand written texts, identify important information, and construct meaning from various sources. This research employed a quasi-experimental design involving two groups: an experimental class and a control class. The experimental class was taught using the Round Robin strategy as a cooperative learning model, while the control class was taught using a conventional reading aloud strategy. The participants consisted of 59 tenth-grade students selected through cluster sampling. Data were collected through pre-tests and post-tests in the form of multiple-choice questions covering five indicators of reading comprehension: identifying main ideas, identifying specific information, understanding word meaning, identifying references, and making inferences. The results of the study showed that the Round Robin strategy had a significant positive effect on students’ reading comprehension. The mean post-test score of the experimental class (80.44) was higher than that of the control class (74.52). Furthermore, the independent sample t-test revealed a significance value of 0.017, which is lower than the significance level of 0.05, indicating a statistically significant difference between the two groups. These findings suggest that the Round Robin strategy effectively enhances students’ reading comprehension by promoting active participation, cooperative learning, and critical thinking during the learning process